PENGAPLIKASIAN KENDALI SUHU PELTIER DENGAN MENGGUNAKAN KENDALI PID BERBASIS ARDUINO UNO - Vauzia, Farrah (Direktorat Penelitian dan Pengabdian Masyarakat, Universitas Telkom, 2022)
Temperature is one of the inseparable aspects of human life. Nowadays, we can control the temperature for many purposes. For instance, cooler application as a heatsink while equipment is working in high temperature. However, most coolers do not have control systems and work at full power. Hence, a Peltier cooling system with a PID controller is realized. This system works by utilizing the Peltier effect and PID control to maintain temperature as desired. DHT22 sensor will read the temperature at the Peltier where the outputs are connected to the controller for data processing and adjust the output for Peltier. The method used is the Ziegler-Nichols type 1. The final result of the control parameter experiments are Kp = 10, Ti = 0,001, and Td = 1 with response of overshoot 0,9 %, rise time 75,139 s and steady-state error 0 %. This system is also able to maintain the temperature after being given interference.